2021
DOI: 10.3390/pr9091589
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Salvianolic Acid B in Acetic Acid-Induced Experimental Colitis in a Mouse Model

Abstract: In its prominent experimental studies salvianolic acid B (Sal B) is novel because of its well-defined, common physiological effects, which include anti-inflammatory, anti-depressant, cardioprotective, DNA protective, neuroprotective and hepatoprotective activity in experimental animals. Initially, Sal B was studied for its anti-inflammatory properties, used as a remedy for a wide range of disease conditions, but its specific efficacy on inflammatory bowel disease is still unclear. The aim of this current study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…This observation is in line with findings from Govindarasu et al, where reduced SOD activity was noted in SABtreated colon tissues. 21 Consequently, SAB-induced down-regulation of SOD may spare β-catenin levels, thereby preserving hair growth. However, further research is required to elucidate SAB's direct impact on β-catenin expression.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in line with findings from Govindarasu et al, where reduced SOD activity was noted in SABtreated colon tissues. 21 Consequently, SAB-induced down-regulation of SOD may spare β-catenin levels, thereby preserving hair growth. However, further research is required to elucidate SAB's direct impact on β-catenin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, high doses of salvianolic acid A (17) increased colon length and improved colonic tissue structure and colonic tight junction injury [ 130 ]. In addition, salvianolic acid B ( 19 ) could increase the levels of SOD, catalase (CAT), and glutathione (GSH) in the colonic mucosa and decrease the levels of peroxidase myeloperoxidase (MPO) and MDA, which can improve free radical scavenging and antioxidant capacity, decrease lipid peroxidation, and attenuate colonic ulceration, thus improving UC [ 131 ]. Moreover, another study showed that rosmarinic acid ( 13 ) significantly ameliorated DSS-induced colonic inflammation in mice by inhibiting the expression of pro-inflammatory cytokines and inflammatory mediators through the dual inhibition of NF-κB and STAT3 activation [ 132 ].…”
Section: Effects Of Salvianolic Acid Components On Immune Systemmentioning
confidence: 99%
“…Despite the anti-ulcer efficacy of this chemically synthetic drug (omeprazole), it has some downsides, with risk factors for asymptomatic hypomagnesemia, hypocalcemia, and hypernatremia [16]. Therefore, researchers are racing against the time to find a natural compound or medicinal herb to be a substitute for those chemically synthetic PPIs [17][18][19].…”
Section: Introductionmentioning
confidence: 99%